Pembelajaran Konstruktivistik Project Based Learning Berorientasi Kontekstual untuk Meningkatkan Karakter Profetik Profesional Mahasiswa Pendidikan Biologi - Muhfahroyin, Muhfahroyin; Santoso, Handoko (Bioedusiana: Jurnal Pendidikan Biologi, 2024)
Professional prophetic character is religious values based on prophetic traits, including aspects of Siddiq, Amanah, Fathanah, and Tabligh characteristics. Biology education students as prospective biology teachers in secondary schools have the potential to develop themselves into prophetic teachers by equipping them with professional skills in pedagogical, professional, personality and social competencies. In implementing contextual learning, students can explore their potential constructively in a professional prophetic context. This study aims to determine the increase in the professional prophetic character of students in contextually oriented Project Based Learning constructivist learning. The research was carried out in the even semester of the 2021/2022 Academic Year. The subjects of this study were Semester 6 (six) students who took the Biology Development course in SMA. Learning activities carried out in the form of contextually teaching material development activities, contextual presentations, contextual discussions, doing assignments, and working together contextually. During the learning process students carry out good qualities as a manifestation of professional prophetic character which includes Shiddiq, Fathonah, Amanah, and Tabligh. The research results show an increase in professional prophetic aspects in constructivist learning contextually oriented Team Based Projects. This increase can be seen from the Shiddiq aspect which increased by 30.61%, from the Amanah aspect by 32.17%, from the Fathanah aspect by 44.92%, and from the Tabligh aspect by 24.63%. Based on this research, the researcher suggests that for constructivist learning the Project Based Learning can be integrated contextually to improve the student's professional prophetic aspects.